2017
DOI: 10.1159/000464409
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in Solitary Thyroid Nodules: Evaluation of Risk Factors

Abstract: Background: The aim of the present study was to evaluate patients with suspicious solitary nodules undergoing bilateral total thyroidectomy for the presence of malignancy. Patients and Methods: 141 patients with true solitary thyroid nodules who underwent bilateral total thyroidectomy at the Dr. Abdurrahman Yurtaslan Ankara Oncology Hospital between 2008 and 2013 were retrospectively evaluated. Parameters including demographics, ultrasonographic findings, and laboratory values were analyzed. Results: When the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
(20 reference statements)
0
10
1
1
Order By: Relevance
“…The composition, echogenicity, orientation, margin, and shape were automatically analyzed by the CADs. Microcalcifications are also regarded as a suspected feature of thyroid malignancies [20, 21]. Vascularity could also be a complementary tool in the differentiation of thyroid nodules [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…The composition, echogenicity, orientation, margin, and shape were automatically analyzed by the CADs. Microcalcifications are also regarded as a suspected feature of thyroid malignancies [20, 21]. Vascularity could also be a complementary tool in the differentiation of thyroid nodules [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In the other hand, various studies have reported that nodule size and nodule shape were not significant risk factors and did not affect the risk of malignancy.…”
Section: Resultsmentioning
confidence: 94%
“…However, recent studies have suggested higher rates of underlying malignancy in hyperthyroidism. 9 Therefore, the present study evaluated the effect of hyperthyroidism on risk of thyroid malignancy in patients undergoing thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8 However, recent studies have shown increased rates of thyroid cancer in patients with hyperthyroidism. [9][10][11] In addition, the malignancy seen in these patients has been shown to demonstrate aggressive histologic features. 10,12 The American Thyroid Association's (ATA) recommendation for the management of patients with hyperthyroidism because of Graves' disease is antithyroid drugs, followed by radioactive iodine ablation (RAI) or thyroidectomy for definitive management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation